Association between the starting age of non-parental Early Childhood Education and Care (ECEC), and psycho-social problems in adolescence in West and East Germany – a natural experiment using data from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) - Ying Zhou; Annelene Wengler; Gabriele Doblhammer (BMC Psychology, 2023)
Abstract Introduction The study aimed to investigate the association between the start age of non-parental Early Childhood Education and Care (ECEC) and psycho-social problems in adolescence. The similarities and differences between West and East Germany were also investigated in a natural experiment. Methods Our sample consisted of 1022 children (621 from West Germany, 401 from East Germany) aged 3–4 years at wave 2003–2006 that were followed up to wave 2014–2017 as adolescents (mean ± SD age = 14.4 ± 0.03 years) in the KiGGS study. The psycho-social problems were measured by the parent-reported Strengths and Difficulties Questionnaire (SDQ) at wave 2014–2017. Linear regression was used to explore the relationship between ECEC-start-age and psycho-social problems in adolescence in Germany, and stratified by West and East Germany. Results Those who started ECEC between 2 and 3 years old (reference) had the lowest scores of psycho-social problems in the whole Germany and in West Germany in adolescence. In comparison, those who started ECEC older than 3 years old had higher scores of internalizing psycho-social problems in both West Germany (with statistically significant results) and East Germany (with a relatively larger effect size but insignificant results). Those who started ECEC younger than 1 year old had statistically significant higher scores for externalizing psycho-social problems in West Germany, even though less children started ECEC younger than 1 in West Germany compared to East Germany. This significant association was not found in East Germany. Those who started ECEC between 1 and 2 years old tended to have higher scores of externalizing psycho-social problems in both West and East Germany. Conclusion The results suggest that if children start ECEC older than 3 years or younger than 2 years, more attention needs to be given to internalizing or externalizing psycho-social problems respectively. The regional differences for children younger than 1 year old may suggest a selection effect in West Germany where only fewer parents bring babies to ECEC, while the regional similarities for children over 3 years old indicate the importance of providing access to ECEC for children over 3 years old.